Aggregation behavior of aqueous dioctadecyldimethylammonium bromide/monoolein mixtures: a multitechnique investigation on the influence of composition and temperature - Oliveira, I. M. S. C. (2012)
A recently described non-viral gene delivery system [dioctadecyldimethylammonium bromide (DODAB)/ monoolein (MO)] has been studied in detail to improve knowledge on the interactions between lamellar (DODAB) and non-lamellar-forming (MO) lipids, as a means to enhance their final cell transfection efficiency. Indeed, the morphology, fluidity, and size of these cationic surfactant/neutral lipid mixtures play an important role in the ability of these systems to complex nucleic acids. The different techniques used in this work, namely dynamic light scattering (DLS), fluorescence spectroscopy, differential scanning calorimetry (DSC), cryogenic transmission electron microscopy (cryo-TEM), light microscopy (LM), and surface pressure–area isotherms, allowed fully characterization of the phase behavior and aggregate morphology of DODAB/MO mixtures at different molar ratios. Overall, the results indicate that the final morphology of DODAB/MO aggregates depends on the balance between the tendency of DODAB to form zero-curvature bilayer structures and the propensity of MO to form non-bilayer structures with negative curvature. These results also show that in the MO-rich region, an increase in temperature has a similar effect on aggregate morphology as an increase in MO concentration.